Pelatihan Pembuatan Ilustrasi Cerita Anak Bagi Guru Sekolah Dasar - Wigati Yektiningtyas; Ince Rezky Naing (JURNAL PENGABDIAN PAPUA, 2026)
Based on readability tests at several schools, picture storybooks were well-liked by students and motivated them to read. However, not many teachers can draw to enhance their work. Meanwhile, illustration fees in Papua are relatively expensive. This community service activity aimed to provide training for teachers to create illustrations for the children's stories. This service activity involved six elementary school teachers in Jayapura City. The activity, conducted from June to July 2025, used a participatory and collaborative method between lecturers, illustrators as trainers, and students. The chairperson and members collaborated to prepare participants, trainers, training materials, story materials, and training designs. The trainers taught how to create illustrations using Canva based on stories prepared by the team. This activity resulted in three picture storybooks: "Lula and Luli," "Amerensi Boat," and "Betel Leaf from Grandma's Garden." Through the results of the limited readability test, the children understood the stories and enjoyed the pictures in the stories. Furthermore, through this activity, the participants gained insight and knowledge to improve the children's stories they wrote with their own illustrations. They also resolved to disseminate what the learned to their fellow teachers.